Gambaran pH Saliva dan Jumlah Karies pada Siswa Kelas 1 SD Negeri 2 Temuwangi Kabupaten Klaten - Rika Febri Ratnawati; Taadi Taadi; Aryani Widayati (Journal of Oral Health Care, 2017)
Caries is the commonest disorders which may frequently occur as a dental and oral disease. This dental decay can be found on children since they prefer to consume sweets which might cause the existence of dental caries. The acidity of saliva pH can be assumed as a factor emerged dental caries. Saliva is a compound consisted of various liquid produced in the mouth. In order to keep the mouth clean, the adequate amount of saliva is importantly needed.This research is purposed to find out the description of Saliva pH and caries toward first grade students in State Elementary School 2 Temuwangi, Klaten regency. This research can be categorized as descriptive method applying technique of data collection by crossectional approach. All of first grade students in this elementary school are the population of the research. The result shows that participants who have similar degree of saliva acidity dominated by neutral criterion are reflectedby14 female children as much as 82.4% precentage in which 12 students are attaining the age of 7 years old as much as 70.6% percentage. 13 participants have the highest number of caries as much as 76.5% percentage dominated by female participants in which 11 participants are attaining the age of 7 years old as much as 64.7 % percentage. Therefore, the biggest number of saliva acidity within this research is neutral saliva acidity shown by 14 people (82.4%) and the biggest number of caries is on 13 students (76.5%).